CompTIA Network+ Practice Tests Exam N10-009 - Zacker, Craig (John Wiley & Sons, Incorporated, 2024)
Assess and improve your networking skillset with proven Sybex practice tests In the freshly revised Third Edition of CompTIA Network+ Practice Tests Exam N10-009, IT expert and author Craig Zacker delivers a set of accessible and useful practice tests for the updated Network+ Exam N10-009. You'll prepare for the exam, learn the information you need in an industry interview, and get ready to excel in your first networking role. These practice tests gauge your skills in deploying wired and wireless devices; understanding network documentation and the purpose of network services; work with datacenter, cloud, and virtual networking concepts; monitor network activity; and more. This book also offers: Comprehensive coverage of all five domain areas of the updated Network+ exam, including network concepts, implementation, operations, security, and troubleshooting Practical and efficient preparation for the Network+ exam with hundreds of domain-by-domain questions Access to the Sybex interactive learning environment and online test bank Perfect for anyone preparing for the CompTIA Network+ Exam N10-009, the CompTIA Network+ Practice Tests Exam N10-009 is also an indispensable resource for network administrators seeking to enhance their skillset with new, foundational skills in a certification endorsed by industry leaders around the world. And save 10% when you purchase your CompTIA exam voucher with our exclusive WILEY10 coupon code.
Description based upon print version of record
Keywords: Computing Technology Industry Association -- Study guides -- Examinations; Computer networks -- Study guides -- Examinations; Electronic data processing personnel -- Study guides -- Certification